2021
DOI: 10.1186/s13023-021-01819-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory prognosticators of atrophic papulosis (Degos disease): a systematic review

Abstract: Background Degos disease is a rare vascular disorder with a cutaneous-limited form, benign atrophic papulosis (BAP), and a systemic variant, malignant atrophic papulosis (MAP). Despite the poor prognosis of MAP, no study has established features associated with systemic disease. Objectives The aims of this systematic review were to: (1) summarize clinical features and treatments implemented for patients with MAP and BAP (2) identify clinical and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 16 publications
5
31
0
Order By: Relevance
“…This fact has been mentioned in the literature and requires further insights and vigilance from physicians of various specialties 18 . Concerning the frequency of involvement of particular internal organs, an equal prevalence of the CNS and the GIT manifestations was observed in the current study, which stands in agreement with our previous work, 4 but not with older studies, in which emphasis has been placed on GIT involvement, which has been reported to be more common 5,8,19–21 . Neurological involvement has been reported more rarely, namely in 19–68.5% of patients 5 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This fact has been mentioned in the literature and requires further insights and vigilance from physicians of various specialties 18 . Concerning the frequency of involvement of particular internal organs, an equal prevalence of the CNS and the GIT manifestations was observed in the current study, which stands in agreement with our previous work, 4 but not with older studies, in which emphasis has been placed on GIT involvement, which has been reported to be more common 5,8,19–21 . Neurological involvement has been reported more rarely, namely in 19–68.5% of patients 5 .…”
Section: Discussionsupporting
confidence: 91%
“…A striking trend towards a more frequent MAP diagnosis (59%) than in the previous study (29%) 4 was observed. In a literature review, 63.8% of patients had MAP and 36.2% suffered from BAP, 5 rates which are similar to our current results. This fact could be explained by the larger number of patients monitored now and a growing awareness of the disease among physicians.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations